Analysis of risk factors for pelvic organ prolapse in females after hysterectomy - Olga V. Soloveva; Valerii G. Volkov (IP Berlin A.V., 2022)
Aim. To identify risk factors for pelvic organ prolapse in females after hysterectomy. Materials and methods. A cross-sectional study from August 2019 to October 2021 in women after hysterectomy for benign neoplasms (n=91) analyzed history, outpatient medical record data, and clinical examination findings. Pelvic organ prolapse was assessed using the POP-Q (Pelvic Organ Prolapse Quantification) international classification. All patients were divided into two groups: Group 1 (n=61) included patients with the pelvic organ prolapse; Group 2 (n=30) included patients without the pelvic organ prolapse. Results. Post-hysterectomy pelvic organ prolapse was observed in 67% (61/91) patients, including grade 1 in 49.2% (30/61), grade 2 in 36.0% (22/61), and grade 3 in 14.8% (9/61). The significant risk factors include obstetric trauma (41 83.7%; odds ratio OR 5.6, 95% confidence interval CI 2.114.8; p=0.00034), age (49 84.5%; OR 19.7, 95% CI 0.5990.831; p=0.00001) and lifestyle associated with weight lifting (32 72.1%; OR 9.8, 95% CI 0.63.9; p=0,00267). No statistically significant differences were observed when comparing the prolapse rate with the presence of connective tissue dysplasia and somatic disorders. Analysis of cumulative risk factors showed significant differences; in Group 1, the mean number of risk factors was 4.61.6 (95% CI 3.26.1), and in Group 2, 2.71.8 (95% CI 2.53.8), t-test value was 6.76, p0.001. Conclusion. Genital prolapse occurs in more than 1/2 of females after hysterectomy. The most significant risk factors are obstetric trauma, age, and a lifestyle associated with weight lifting. The incidence of pelvic organ prolapse increases when several risk factors are combined.